Understanding the molecular targets of a cysteine-rich peptide from Theobroma cacao using a chemoproteomics approach - Nair, Keloth Sonia (Nanyang Technological University, 2022)
Cysteine-rich peptides (CRPs) of 2-6 kDa in size are hyperstable and are found in many plant species. Theobroma cacao is a plant rich in CRPs. Cacao, the main ingredient in chocolate, is obtained from the cacao beans of Theobroma cacao. Apart from being a confectionary indulgence, chocolate has historically been consumed for medicinal and therapeutic uses. To date, majority of the studies on cacao are focused on small secondary metabolites. Here, we report the identification of a CRP, cocotide tC1, derived from the cacao beans of Theobroma cacao. Cocotide tC1 was shown to be a proteolytically stable 8-cysteine CRP. To characterize its molecular targets, we chemically synthesized and oxidatively folded N-terminal biotinylated cocotide tC1. This chemical probe was then used for affinity-enrichment mass spectrometry to identify interacting proteins. Cocotide tC1 was found to interact with three groups of proteins associated with iron-sulfur clusters, the mTOR signaling pathway, and thermogenesis. In this study, we focused on the association with iron-sulfur clusters and found that cocotide tC1 exhibits iron-binding and antioxidant activities associated with Ferric Reducing Antioxidant Power. In conclusion, we identified cocotide tC1, a novel 8-cysteine CRP from Theobroma cacao, and demonstrated its hyperstability and potential iron-binding and antioxidant activities.